The influence of seat heights and foot placement positions on postural control in children with cerebral palsy during a sit-to-stand task - Medeiros D.L.D.* (2015)
© 2015 Elsevier Ltd.This paper aimed to analyze, from both a kinetic and kinematic perspective, the postural control of children with cerebral palsy (CP) able to independently perform the sit-to-stand (STS) task (ICP) and children who needed support (SCP) typically developing children during the STS; and also investigate the influence of seats heights and foot placement positions on postural control of these children. Fourteen children with CP and fourteen typically developing controls were recruited. Based on the Gross Motor Function Classification System (GMFCS) the children with CP were divided into ICP (level I) and SCP (levels II and III). Balance was assessed using the Pediatric Balance Scale. Motor function was rated using the GMFCS. Kinematic and kinetic data were recorded and analyzed during the STS task at two different seat heights and foot placement positions. The SCP exhibited significantly less balance according to the PBS and smaller displacement of their center of pressure (COP) in anteroposterior (COPAP) and mediolateral (COPML) direction relative to the other two groups. ICP demonstrated significant greater in the COPML displacement than the other groups. Children with CP required more time to complete the STS than controls. Those in the SCP group had lower linear displacement of the shoulder and knee than others during the STS task. During the high bench condition, the linear displacements of the shoulder and knee were reduced also. We conclude that the SCP has less COPAP and COPML oscillation, what means the better postural control during STS than the other two groups, which may be related to the support provided. The ICP exhibited greater COPML oscillations than controls, suggesting that they utilized different strategies in the frontal plane during the STS task. The seat height and foot placement did not influence postural control in children with CP, at least in terms of kinetic parameters. Seat height influenced the kinematic variables, with a high bench reducing linear displacement of the shoulder (vertical and horizontal) and knee (vertical) both in children with CP and control children.